Anxiety for job application among undergraduate students at Faculty of Arts - Tiensirirerk, Panitnart; Suppapitiporn, Siriluck (Chulalongkorn Medical Journal, 2021)
Background: Arts degrees are questioned of being useless degree for having no specific career path for new graduates. The degrees with no specific jobs combining varies subjects such as art, humanities, and social sciences may cause anxiety during the job search process upon graduation. Objective: To explore the level of anxiety of job application and factors related to anxiety of job application among undergraduate students at the Faculty of Arts at a university in Thailand. Methods: A cross-sectional design was employed with participation of 296 students in the Faculty of Arts, Chulalongkorn University. A structured questionnaire was applied to ask about demographic information, anxiety of job application, self-esteem (Thai version of the Rosenberg Self-Esteem Scale), personality traits (Thai version of Big Five Inventory), and coping strategy (Thai version of Coping Strategy). Results: Thirty-five point five percent of students with high anxiety job application were detected. The average score of anxiety of job application was 66.69. High level of anxiety of job application was significantly correlated with medical problems, family financial status, types of careers interests, attitude about current job search situations, lower self-esteem level, higher scores of neuroticism, lower scores of extraversion, lower scores of agreeableness, lower scores of problem-focused strategy, and higher scores of avoidance coping strategy. Conclusion: Students with higher self-esteem, higher scores of extraversion and agreeableness personality, and problem-focused strategy tended to be less anxious of job application. These results therefore suggested the need for an action from related parties proactively increasing students’ self-esteem and required skills for dealing with anxiety of job application.